2016
DOI: 10.1002/pon.4239
|View full text |Cite
|
Sign up to set email alerts
|

Financial cost of lymphedema borne by women with breast cancer

Abstract: ObjectiveOur study examines the financial cost of lymphedema following a diagnosis of breast cancer and addresses a significant knowledge gap regarding the additional impact of lymphedema on breast cancer survivors.MethodsAn online national survey was conducted with 361 women who had either breast cancer without lymphedema (BC) (group 1, n = 209) or breast cancer with lymphedema (BC+LE) (group 2, n = 152). Participant recruitment was supported by the Breast Cancer Network Australia and the Australasian Lymphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 24 publications
5
63
0
2
Order By: Relevance
“…The presence of secondary upper-quadrant lymphedema (SUQL) can lead to significant morbidity, activity and participation restrictions, reduced quality of life, and economic hardship 26. In 2016 alone, it was estimated that 1.6 million people in the United States had a diagnosis of cancer,7 many involving the upper quadrant, and thus a large number of cancer survivors are at risk of developing SUQL.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of secondary upper-quadrant lymphedema (SUQL) can lead to significant morbidity, activity and participation restrictions, reduced quality of life, and economic hardship 26. In 2016 alone, it was estimated that 1.6 million people in the United States had a diagnosis of cancer,7 many involving the upper quadrant, and thus a large number of cancer survivors are at risk of developing SUQL.…”
Section: Introductionmentioning
confidence: 99%
“…Having quality insurance was associated with minimizing burdensome out‐of‐pocket costs, and those with the lowest economic burden believed it was because they had “good insurance.” Patients incur substantial out‐of‐pocket costs and may not know whether such costs could be covered by insurance . This was especially true among those with lymphedema; although the Patient Protection and Affordable Care Act was successful in expanding affordable insurance coverage for cancer‐related care, it did not address the adverse treatment effects of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients incur substantial outof-pocket costs and may not know whether such costs could be covered by insurance. 45 This was especially true among those with lymphedema; although the Patient Protection and Affordable Care Act was successful in expanding affordable insurance coverage for cancerrelated care, 46 it did not address the adverse treatment effects of cancer. Studies before the 2010 Affordable Care Act reported that financial burden created worry and anger when tools for lymphedema management were not covered by insurance.…”
Section: Insurancementioning
confidence: 99%
“…Moreover, according to a US study conducted on the SEER‐Medicare database, mastectomy associated with reconstruction would appear to increase the risk of complications and the cost of treatment compared to breast‐conserving surgery followed by radiotherapy sessions . Further complications, such as the presence of lymphoedema, may have an additional cost …”
Section: Discussionmentioning
confidence: 99%
“…31 Further complications, such as the presence of lymphoedema, may have an additional cost. 32 Internal controls were performed to take into account coding errors in the SNDS, which was developed for economic and not epidemiological purposes. Some in situ cancers were classified as invasive cancer.…”
Section: F I G U R Ementioning
confidence: 99%